Korelasi Praktek Sukuk Ijarah dengan Investasi di Indonesia: Bentuk Perspektif Hukum Syariah - Winda Fitri (Wajah Hukum, 2022)
At this time, there were many investors interested in sukuk in investing because sukuk gave higher returns than deposit rates with a clearly smaller risk. Sukuk with the type of ijarah contract are the most popular types of sukuk, both since they were first issued and until now during this Covid-19 pandemic. This is sufficient from the good market absorption of sukuk where in 2020 there will be 162 sukuk series issued and 64% Ijarah contracts. However, in practice this sukuk was found to be incompatible with the sharia principles that were implanted at the beginning, where the sukuk showed a direction similar to the practice of conventional bonds. From the existing background, the purpose of this research are the concept of sukuk as an investment, Islamic principles that apply in Ijarah Islamic bonds. The discussion of this problem uses normative juridical research methods and descriptive qualitative analysis through secondary data. The results of data analysis show that in society, the practice of Ijarah contracts that are not pure and leads to the muntahiya bi al-tamlik contract is similar to the mechanism offered in conventional bonds in general so that it does not run in accordance with sharia principles.